Hindu theology in early modern South Asia : the rise of devotionalism and the politics of genealogy - Okita, Kiyokazu, 1980- (Oxford theology and religion monographs., 2014)
Kiyokazu Okita explores the historical development of a Hindu devotional movement in early modern South Asia. He provides a rigorous philological analysis of Sanskrit texts, which is combined with a detailed examination of the specific historical circumstances which led to their formation.